Complete utilization of waste lignin: preparation of lignin-derived carbon supports and conversion of lignin-derived guaiacol to nylon precursors. Issue 16 (7th June 2022) - Lee, Jun Gyeong; Lee, Shinjae; Lee, Hojeong; Kurisingal, Jintu Francis; Han, Seung Hyun; Kim, Yong Hwan; An, Kwangjin
Abstract : A new catalytic process was developed to produce raw materials for nylon production utilizing 100% of waste lignin emitted from industrial processes. Abstract : The valorization of waste lignin for the production of high value-added chemicals is energetically and environmentally important. In this study, a new catalytic process was developed to produce raw materials for nylon production utilizing 100% of waste lignin emitted from industrial processes. Guaiacol, extracted from technical lignin, was converted to phenol through a hydrodeoxygenation reaction over carbon-supported MoO2 catalysts. The extracted lignin oil served as a carbon source to prepare lignin-derived porous carbons possessing an interconnected porous structure with a large pore size and volume via a nanocasting method. The high dispersion of MoO2 deposited on the porous carbon support enables a high guaiacol conversion (98.4%) and high phenol selectivity (73.7%) compared to those of a typical activated carbon support. The resulting phenol was selectively converted to cyclohexanone or cyclohexanol, depending on the controlled hydrogenation environments over carbon-supported Pd catalysts. The remaining solid residue during lignin extraction was also used as a carbon support to load Pd catalysts. The produced cyclohexanone and cyclohexanol were further converted to caprolactam and adipic acid, the main reagents used to produce nylon-6 and nylon-6, 6 fibres, respectively. This process was demonstrated using real kraft and Klason lignin released from industry. The mass of guaiacol produced from 20 g of kraft lignin was 0.07 g, yielding either 0.032 g caprolactam or 0.043 g adipic acid, with a total yield of 0.15–0.25%. This study sheds light on utilizing waste lignin as a resource by producing not only guaiacol raw material for the production of high value-added nylon, but also a carbon support used for catalytic conversion.